Transition I efficiency and victory in volleyball matches - Herbert Ugrinowitsch; Guilherme Menezes Lage; Suziane P. dos Santos-Naves; Leandro N. Dutra; Maria Flávia S. P. Carvalho; Alessandra Aguilar Coca Ugrinowitsch; Rodolfo N. Benda (Universidade Estadual Paulista (UNESP), 2014)
The present study investigated the correlation between Transition Iwith victory in volleyball matches. The 2002 South-American Youth Men's Championship was recorded and the Transition I was analyzed and classified as negative, null or positive. Results of the efficiency in Transition I was calculated using t test for independent samples and compared to the efficiency between teams during each set and matches. Spearman correlation assessed the relationship between efficiency in each set and results of the matches with the final ranking in the championship. The results showed that the winning teams exhibited higher efficiency in Transition I, as well as a positive relationship of higher efficiency in Transition I with all of their results. The higher efficiency in Transition I is related to victory in volleyball matches.